Boundary stabilization of extensible and unshearable marine risers with large in-plane deflection. (March 2017) - Do, K.D.; Lucey, A.D.
Abstract: This paper proposes a constructive design of boundary controllers for globally (practically) K ∞ -exponential stabilization of extensible and unshearable marine risers with large in-plane deflection under sea loads. Linearization or Maclaurin expansion of the strain and cross section rotation are not required. The control design is based on the Lyapunov direct method. Well-posedness and stability of the closed-loop system are analyzed by two Lyapunov-type theorems developed for study of existence and uniqueness, and stability of nonlinear evolution systems in Hilbert space.